2020
DOI: 10.1021/acs.jpclett.9b03275
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization Dynamics and Coherent Spin Manipulation of a Propeller Gd(III) Complex with the Smallest Helicene Ligand

Abstract: A homoleptic gadolinium(III) complex with the smallest helicene-type ligand, 1,10-phenanthroline- N , N ′-dioxide (phendo) [Gd(phendo) 4 ](NO 3 ) 3 · x MeOH (phendo = 1,10-phenanthroline- N , N ′-dioxide, MeOH = methanol), shows slow relaxation of the magnetization characteristic for Single Ion Magnets (SIM), despite negligible m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 59 publications
3
34
1
Order By: Relevance
“…Due to the presence of two relaxation processes for both undiluted compounds, the dynamic magnetic properties of the solid state diluted samples Er2% and Yb2% were also studied (the solid state dilution suppresses the dipole-dipole interactions between the Er III or Yb III centers enabling a straightforward analysis of the AC data). According to our previous study of the isostructural Gd III -based complex 39 the solid state dilution lower than 3% effectively switches off the dipole-dipole interactions. The exact concentrations of the Er III in Er2% and Yb III in Yb2% were determined by ICP-OES analysis (see Table S5 in the ESI for details).…”
Section: Magnetic Propertiesmentioning
confidence: 93%
See 2 more Smart Citations
“…Due to the presence of two relaxation processes for both undiluted compounds, the dynamic magnetic properties of the solid state diluted samples Er2% and Yb2% were also studied (the solid state dilution suppresses the dipole-dipole interactions between the Er III or Yb III centers enabling a straightforward analysis of the AC data). According to our previous study of the isostructural Gd III -based complex 39 the solid state dilution lower than 3% effectively switches off the dipole-dipole interactions. The exact concentrations of the Er III in Er2% and Yb III in Yb2% were determined by ICP-OES analysis (see Table S5 in the ESI for details).…”
Section: Magnetic Propertiesmentioning
confidence: 93%
“…4,32,33 Moreover, deep understanding of relaxation mechanisms for SIMs which do not possess pure mJ ground states is also important from the point of view of molecular qubit candidates design, demonstrated for several non-dysprosium complexes so far. [34][35][36][37][38][39][40] Herein we present a thorough magnetic and EPR study of three lanthanide-based SIMs from the family of [Ln(phendo)4](NO3)3•xMeOH (Ln = Gd (Gd), Er (Er), Yb (Yb), phendo = 1,10-phenanthroline-N,N'-dioxide). The complexes show four-bladed propeller-like geometry enforced by the helicene-type phendo ligands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic measurements showed that gadolinium (II and VII) and dysprosium (IX) complexes behave as field-induced SMM. The gadolinium(III) complexes can exhibit magnetic relaxation [ 56 , 57 , 58 , 59 , 60 ] either due to weak anisotropy [ 56 ] or a low rate of relaxation processes other than Orbach relaxation. The observed effect requires more thorough studies.…”
Section: Discussionmentioning
confidence: 99%
“…4,32,33 Moreover, deep understanding of relaxation mechanisms for SIMs which do not possess pure mJ ground states is also important from the point of view of molecular qubit candidates design, demonstrated for several non-dysprosium complexes so far. [34][35][36][37][38][39][40] Herein we present a thorough magnetic and EPR study of three lanthanide-based SIMs from the family of [Ln(phendo)4](NO3)3•xMeOH (Ln = Gd (Gd), Er (Er), Yb (Yb), phendo = 1,10-phenanthroline-N,N'-dioxide). The complexes show four-bladed propeller-like geometry enforced by the helicene-type phendo ligands.…”
Section: Introductionmentioning
confidence: 99%